ANALISIS DAMPAK KEBIJAKAN TUNJANGAN KINERJA (Studi Kasus di Badan Kepegawaian Negara) - Kusumaningsih, Akis; Dwimawanti, Ida Hayu; Hidayat, Zainal (Journal of Public Policy and Management Review, 2015)
Performance Benefits Policy is defined as a function of the successful implementation of bureaucratic reforms on the basis of performance has been achieved by an employee. Problems that occur related to Performance Benefits Policy is the lack of technical regulations in granting allowances performance, so that the amount of allowances performance given to each agency is different and Performance Benefits rational scale when state finances in an unstable state is also not yet considered. Performance Benefits provision problems in NCSA is that provision still based on the workload and the strategic location of agencies, allowances nominal amount of the performance is still not feasible, service and discipline that has not been good because there is no professional human resources and a lack of innovation. The purpose of this research is to identify and analyze the impact of performance benefits against the Job Performance, Work Culture and Employees Fulfillment. Data collection techniques with questionnaires, interviews and observations, the data is processed and analyzed quantitatively. The results showed the perceived impact of employees after the Performance Benefits Policy. Impact on Job Performance in general is good with a percentage of 70%, it is associated with increased quality of work and timeliness in completing the work. Impact on Work Culture is generally sufficient to the percentage of 71%, it is associated with improvement in employee behavior. And the impact on Meeting the Needs of employees in general simply by percentage (66.1%). However, this effect has not been entirely positive because they still need some improvements related to the quantity of work produced by employees, the attitude of employees in work as well as various other aspects in fulfilling the needs of employees. Suggestions from this study is the need for changes to the criteria for the calculation of provision benchmarks on performance benefits, improved communication among employees as well as doing repairs to the weaknesses in the system of performance allowance.